2022
DOI: 10.1177/00031348221105596
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Screening for Colorectal Cancer Based on Limited Language Proficiency

Abstract: Background This study analyzes the association between limited language proficiency and screening for colorectal cancer. Methods This is a retrospective cohort study from the 2015 sample of the National Health Interview Survey database utilizing univariate and multivariate regression analysis. The study population includes subjects between 50 and 75 years of age. The main outcome analyzed was rates of screening colonoscopies between limited English-language proficiency (LEP) subjects and those fluent in Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Prior studies found CRC screening to range from 34 to 43 percent in adults with LEP between 2014 and 2016 ( Cataneo et al, 2022 , Ramirez et al, 2023 ). Similarly, we found 31.6 % of adults 45–75 with LEP (40.5 % of those aged 50–75 with LEP) to be up-to-date with CRC screening, suggesting that screening has not risen in adults with LEP in the past 7 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies found CRC screening to range from 34 to 43 percent in adults with LEP between 2014 and 2016 ( Cataneo et al, 2022 , Ramirez et al, 2023 ). Similarly, we found 31.6 % of adults 45–75 with LEP (40.5 % of those aged 50–75 with LEP) to be up-to-date with CRC screening, suggesting that screening has not risen in adults with LEP in the past 7 years.…”
Section: Discussionmentioning
confidence: 99%
“…Adults with LEP are known to have less access to health care services ( Ponce et al, 2006 , Gulati and Hur, 2022 ), lower quality of care ( Karliner et al, 2012 , John-Baptiste et al, 2004 , Lindholm et al, 2012 ), and report worse dissatisfaction with care ( Pippins et al, 2007 , Weech-Maldonado et al, 2003 ). In 2015, 34 % of US adults with LEP reported ever having a screening colonoscopy ( Cataneo et al, 2022 ), while 43 % were up-to-date with CRC screening as of 2016 compared to 61 % of those without LEP ( Ramirez et al, 2023 ). Adults with LEP may be less likely to be screened due to difficulty communicating with their clinicians ( Berdahl and Kirby, 2019 ) and less access to preventive healthcare ( Ramirez et al, 2023 , DuBard and Gizlice, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of knowledge about CRC and CRC screening modalities, lack of physician's recommendation for screening, fear of the screening process, fear of results, cancer fatalism, and distrust of the medical system have also been identified as powerful predictors of low CRC screening adherence in API and other minority populations 35‐37 . English language proficiency and knowledge of US healthcare systems are additional barriers to CRC screening in Asian and Hispanic immigrant groups 38 . Lack of culturally appropriate cancer education resources, unintended bias exercised by providers, discrimination and structural racism experienced by patients are also likely key contributors to the observed differences in CRC burden among minority groups.…”
Section: Discussionmentioning
confidence: 99%
“…Language-based disparities have been described in various domains of health care. Cataneo et al (10), using the National Health Interview Survey, showed that patients with limited English proficiency (particularly those who identified as Hispanic) had lower rates of fecal occult blood sampling for colorectal cancer screening, lower rates of physician recommendation for colonoscopy, and lower rates of receiving screening colonoscopies. In the emergency department, Spanish-speaking patients have been shown to receive lower acuity triage scores using the Emergency Severity Index compared with English-speaking patients (11).…”
Section: Discussionmentioning
confidence: 99%